Analytical Modelling of the Pullout Behavior of Synthetic Fibres Treated with Nano-silica. (2015) - Radi, Enrico; Lanzoni, Luca; Sorzia, Andrea
Abstract: An accurate one-dimensional analytical model for simulating the pullout process of synthetic fibres from a cement matrix is proposed in the present study in order to shed light on the ductile behavior exhibited by Fibre Reinforced Concrete (FRC) members. The proposed model is able to predict the non linear relation between the applied tensile load and the fibre displacement and is particularly suitable for synthetic fibres that may exhibit large axial elongation and slip-hardening interface behavior. Indeed, the balance conditions between the axial load and the shear stress arising on the fibre surface in frictional contact with the matrix are imposed on the deformed configuration. The frictional bond strength is assumed to increase with slippage distance as a consequence of the increasing abrasion of the fibre surface occurring for polymeric fibres that have been subjected to surface treatments. The model is also suitable for metallic fibres if constant friction or slip-softening interface behavior is assumed instead. The results provided by the proposed model are compared with the results obtained from pullout tests performed on polymeric fibres embedded in a cement matrix, both for treated and untreated fibres. After conveniently setting the constitutive parameters, the model proves to be able to predict the experimental curves accurately.